Evaluation and Screening of Hypoglycemic Activity of Total Ginsenosides GBE-5 Fraction From Panax Ginseng Berry Based on UHPLC–MS Metabolomics - Wang, Heyu; Tong, Yu; Wang, Anqi; Li, Ying; Lu, Bofan; Li, Hui; Jiao, Lili; Wu, Wei (Frontiers in Nutrition, 2022)
Objective: Ginseng berry (GB) was the mature fruit of medicinal and edible herb Panax ginseng C. A. Meyer with significant hypoglycemic effect. Ginsenoside was the main hypoglycemic active component of GB. Evaluating and screening the effective components of GB was of great significance to further develop its hypoglycemic effect. Methods: The polar fractions of ginseng berry extract (GBE) were separated by solvent extraction, and identified by Ultra High Performance Liquid Chromatography - high resolution Mass Spectrometry (UHPLC-MS). The insulin resistance model of HepG2 cells was established, and the hypoglycemic active fraction in GBE polar fractions were screened in vitro. Rat model of type 2 diabetes mellitus (T2DM) was established to verify the hypoglycemic effect of the GBE active fraction. Metabolomic study based on UHPLC-MS was used to analyze the differential metabolites in the serum of T2DM rats after 30 days of intervention with hypoglycemic active GBE fraction. KEGG metabolic pathway enrichment analysis was used to study the main metabolic pathways involved in the regulation of hypoglycemic active parts of GBE. Results: It was found that GBE - 5 fraction had better hypoglycemic activity than other GBE polar fractions in vitro cell hypoglycemic activity screening experiment. After 30 days of treatment, the fasting blood glucose value of T2DM rats decreased significantly by 34.75%, indicating that it had significant hypoglycemic effect. 18 differential metabolites enriched in KEGG metabolic pathway were screened and identified in the rat serum from T2DM vs GBE - 5 group, and the metabolic pathways mainly involved in regulation include arachidonic acid metabolism, linoleic acid metabolism, unsaturated fatty acid biosynthesis and ferroptosis. Conclusions: The hypoglycemic effect of GBE - 5 fraction was better than that of total ginsenoside of GB. Arachidonic acid metabolism, linoleic acid metabolism, unsaturated fatty acid biosynthesis and ferroptosis were the potential metabolic pathways for GBE - 5 fraction to exert hypoglycemic regulation.